Visually focusing on the far versus the near target during the putting stroke - Mackenzie, S. J.; Foley, S. M.; Adamczyk, A. P. (Journal of Sports Sciences, 2011)
The purpose was to evaluate the traditional method, of visually focusing on the ball, in comparison to focusing on the hole, during the putting stroke. The study design consisted of a pretest, a 4-week practice period, and a posttest. Participants (n = 31, handicap: 18.7 ± 10.4) practised using only one of the two gaze techniques. Testing consisted of having all participants putt using both gaze techniques from both a 1.22 m and a 4 m distance. Five putts were executed for each gaze technique/putt length combination for a total of 20 putts in each testing session per participant. The kinematics of every putting stroke executed during testing (1240 strokes) were captured using a TOMI® system. There was a significant improvement in putting success for both groups following practice (P = 0.001). Practising while visually focusing on the hole, resulted in a statistically significant reduction in putter speed variability in comparison to practising while visually focusing on the ball (P = 0.017). Visually focusing on the hole did not meaningfully (nor statistically) affect the quality of impact as assessed by the variability in face angle, stroke path, and impact spot at the precise moment the putter head contacted the ball.